2007
DOI: 10.1074/mcp.m600179-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Antioxidant Proteins and Hydrolytic Enzymes in Pathogenicity of Penicillium expansum

Abstract: Penicillium expansum, a widespread filamentous fungus, is a major causative agent of fruit decay and may lead to the production of mycotoxin that causes harmful effects on human health. In this study, we compared the cellular and extracellular proteomes of P. expansum in the absence and presence of borate, which affects the virulence of the fungal pathogen. The differentially expressed proteins were identified using ESI-Q-TOF-MS/MS. Several proteins related to stress response (glutathione S-transferase, catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 62 publications
2
87
0
Order By: Relevance
“…Previous studies has shown the increased levels of H 2 O 2 in peach (Qin et al 2009), muskmelon (Lacan and Baccou 1998), and tomato (Jimenez et al 2002) fruits. It is also reported that fruit senescence can be reduced by lowering reactive oxygen species (ROS) content by decreasing oxygen concentration in storage environment, whereas H 2 O 2 enhances senescence of fruits (Tian et al 2004;Qin et al 2007). Moreover, high level of oxygen also increases the level of H 2 O 2 in mitochondria (Turrens et al 1982) and affects the antioxidant enzymes activity in fruit and accelerates fruit senescence (Wang et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies has shown the increased levels of H 2 O 2 in peach (Qin et al 2009), muskmelon (Lacan and Baccou 1998), and tomato (Jimenez et al 2002) fruits. It is also reported that fruit senescence can be reduced by lowering reactive oxygen species (ROS) content by decreasing oxygen concentration in storage environment, whereas H 2 O 2 enhances senescence of fruits (Tian et al 2004;Qin et al 2007). Moreover, high level of oxygen also increases the level of H 2 O 2 in mitochondria (Turrens et al 1982) and affects the antioxidant enzymes activity in fruit and accelerates fruit senescence (Wang et al 2005).…”
Section: Introductionmentioning
confidence: 94%
“…1b). As high amounts of ROS usually lead to increased levels of carbonylated proteins in yeast cells [19], a high level of carbonylated proteins were also detected in the D. hansenii cells, and adding exogenous calcium could markedly reduce the protein carbonylation of the yeasts (Fig. 3a, b).…”
Section: Discussionmentioning
confidence: 88%
“…Torres et al (2006) report that variations in the adaptability of yeasts to particular fruit are an important factor in reducing colonization of fungal pathogens, while concentration of yeast inoculum perhaps influences competition for space and nutrients, thereby reducing energy sources for germination of spores and mycelium development and reducing infection. Di grak and Ö zc¸elik (2001), Miedes and Lorences (2006), and Qin, Tian, Chan, and Li (2007) remark that P. italicum requires carbon sources for spore germination and production of enzymes, such as b-1,3-and b-1,6-glucanase, which are essential in the process of infecting fruits. There are other mechanisms in yeast to limit growth of P. italicum.…”
Section: Discussionmentioning
confidence: 99%